DINAMIKA KETENAGAKERJAAN DAN PENYERAPAN TENAGA KERJA DI PEDESAAN JAWA (Kasus di Propinsi Jawa Barat, Jawa Tengah dan Jawa Timur) - SUPRIYATI -; SAPTANA -; SUMEDI - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
The last periode, agricultural sector have to burdensome rural labor absorbtion,consequenly decleaning productivity of labor in agricultural sector and wage rate relativelystagnant. This paper obyective to study : (1) labor dinamic in the macro and micro level; (2)variety kind of labor activity and labor supply in wet land rural area; (3) structure of timelabor allocation in household level; (4) trend of wage rate in wet land rural area. Both inmacro and micro level labor absorbtion in agricultural sector each achieved 68 % and 66 %.Total labor absortion by members household about 75 – 127 days (21-35 %) from timeavaibility. Trend of riel wage rate in two provincial (East Java and Central Java) relativelystagnant (1.03 – 2.03 % per years), so in West Java Provincial to decleaning (0.09 %/years).This fact to indicate shown sign labor over supplay in the rural area. Several recomendationto solve this problem are land use optimalization by higher plant intencity; to developefarming diversification, especially high value commodity; land and farming consolidation;and to develope agroindustry based on local raw material.